2020
DOI: 10.1007/978-3-030-53956-6_59
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-agent Ant Colony Optimization Algorithm for Effective Vehicular Traffic Management

Abstract: An intelligent agent refers to an autonomous entity directing its activity towards achieving goals, acting upon an environment using data obtained with the help of a sensory mechanism. Intelligent agent software is a software system that performs tasks independently on behalf of a user in a networking environment based on user interface and past experiences. By the design of an intelligent sensing software program we can regulate the flow of traffic in a transportation infrastructure network. The problems lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…The PSO algorithm is used to optimize ACO parameters for better performance. With the help of intelligent sensors, SS et al (2020) proposed an ACO meta-heuristicbased model to control and regulate the traffic in transportation networks while minimizing travel time and congestion levels. The authors demonstrate that, due to its dynamic nature, the ACO algorithm is suitable to manage high traffic in big cities.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The PSO algorithm is used to optimize ACO parameters for better performance. With the help of intelligent sensors, SS et al (2020) proposed an ACO meta-heuristicbased model to control and regulate the traffic in transportation networks while minimizing travel time and congestion levels. The authors demonstrate that, due to its dynamic nature, the ACO algorithm is suitable to manage high traffic in big cities.…”
Section: Related Workmentioning
confidence: 99%
“…In the context of an urban road network, ACO can be used to calculate the optimal routes between different locations and can lead to efficient and effective solutions that take into account various factors such as distance, traffic flow and other constraints for the following reasons: One of the main advantages of ACO is that it can handle complex networks with multiple paths and variable conditions because it is a constructive algorithm. By using a pheromone-based approach, the algorithm can adapt to changing traffic conditions and find alternative routes if necessary (SS et al ., 2020). Additionally, ACO is a scalable algorithm that can be applied to networks of varying sizes, making it well-suited for urban road networks that can be quite large and complex (Di Caprio et al ., 2022).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…All the selected intersection measures of effectiveness (MOEs), including vehicle delay, parking rate, and the number of stops, were improved by a fair margin. Sankar and Chandra proposed a multi-agent ACO for effective traffic management on a network level [69]. The authors concluded that the method could be pretty useful in reducing average vehicle delays and traffic congestion under varying traffic conditions.…”
Section: Ant Colony Optimization (Aco)mentioning
confidence: 99%
“…An improved hybrid ACO method was proposed (8,9) for decreasing the congestion in the network in smart cities. This method is also helpful in improving the quality of service during packet transmission.…”
Section: Ant Colony Optimizationmentioning
confidence: 99%